Integrated Analysis of miRNAs Associated With Sugarcane Responses to Low-Potassium Stress - Zhang, Nannan; Feng, Xiaomin; Zeng, Qiaoying; Lin, Huanzhang; Wu, Zilin; Gao, Xiaoning; Huang, Yonghong; Wu, Jiayun; Qi, Yongwen (Frontiers in Plant Science, 2022)
Sugarcane is among the most important global crops and a key bioenergy source. Sugarcane production is always restricted by limited levels of available soil potassium (K+). The ability of plants to respond to stresses can be regulated by a range of microRNAs (miRNAs). However, there was few studies on miRNAs roles in regulating sugarcane responses to K+-deficiency. To understand how miRNAs regulate sugarcane responses to low-K+ stress, we conducted high-throughput miRNA expression profiling. This approach led to the identification of 324 and 42 known and novel miRNAs, respectively, of which 36 were found to be differentially expressed miRNAs (DEMs) when exposed to low-K+ conditions. These results also suggested that miR156-x/z and miR171-x are involved in these responses as potential regulators of lateral root formation and the ethylene signaling pathway respectively. A total of 802 putative targets of these DEMs were further identified, and GO and KEGG enrichment analyses revealed these target mRNAs to be enriched for catalytic activity, binding functions, metabolic processes, plant hormone signal transduction, and mitogen-activated protein kinase (MAPK) signaling. In summary, these data provide an overview of the roles of miRNAs in the regulation of sugarcane response to low-K+ conditions.